Examining Structural Factors Influencing Cancer Care Experienced by Inuit in Canada: A Scoping Review - Huang, Wen Qiu (Université d'Ottawa / University of Ottawa, 2023)
The existing cancer-related disparities among Inuit are rooted in the structural conditions that create health and health care inequities. No comprehensive review currently exists about structural factors that facilitate or hinder Inuit’s access to and experiences with cancer care services in Canada. The overall aim of this scoping review was to synthesize the available published and grey literature on the structural factors that influence cancer care experienced by Inuit in Canada. Guided by the Joanna Briggs Institute (JBI) scoping review methodology, searches were conducted in a number of electronic databases, grey literature sources, and relevant journals. The extracted data were synthesized using thematic analysis and presented using tables and narrative summaries. Quality assessment was performed for each included study on its relevance to Inuit communities. A total of 30 papers were included in this review. The structural factors were identified and described through five categories related to: colonization, as well as health systems, social, economic, and political structures. Addressing the structural barriers that Inuit face in the cancer care trajectory requires a system-wide approach. Thesis results inform health care delivery and nursing practice with the goal of improving health equity for Inuit in cancer care.
Keywords: Inuit; health and wellness; cancer; cancer care; health care; structural factors; Canada